Impact of Nonmedical Adalimumab Switches in a Rheumatology Patient Population - Stefania DelPrete; Krista Dessureault; Molly Bachman; Morgan Merchand; Derek Devine; Amanda G. Kennedy; Julie MacDougall (Journal of Pharmacy Technology, 2026)
Background: Adalimumab is an antitumor necrosis factor agent approved by the U.S. Food and Drug Administration in 2002 for the treatment of various rheumatologic diseases. Recent approval of adalimumab biosimilars presents an important area of study to determine real-world efficacy and cost savings of biosimilars. Objectives: The primary objective was to evaluate the impact of nonmedical, insurance-mandated adalimumab switches on disease activity. The secondary objective was to assess the financial impact of these biosimilar switches. Methods: A retrospective cohort study was conducted of patients with rheumatic diseases who experienced payer-mandated switches to biosimilars. The primary outcome was change in disease activity, defined by provider assessment documented in the electronic health record before switching and at follow-up. Analyses were completed using chi-square or Fisher exact tests for categorical variables and t tests, analysis of variance (ANOVA), or nonparametric equivalents for continuous variables, with P < .05 required for statistical significance. Results: A total of 152 patients were included; among patients controlled at baseline, 84/119 (70.6%) remained unchanged and 35/119 (29.4%) worsened. Among those partially controlled at baseline, 6/17 (35.3%) improved, 7/17 (41.2%) remained unchanged, and 4/17 (23.5%) worsened. Among patients with active disease at baseline, 9/12 (75.0%) improved and 3/12 (25.0%) remained unchanged. Median out-of-pocket copay change was $0. Conclusion: Insurance-mandated switches did not appear to meaningfully impact disease control for most patients. In addition, median out-of-pocket costs did not change after switching. These findings should reassure pharmacists when helping patients with insurance-mandated adalimumab biosimilar switches.